Chronic vagal nerve stimulation has no effect on tachycardia‐induced heart failure progression or excitation–contraction coupling. Issue 2 (20th January 2020) - Radcliffe, Emma J.; Pearman, Charles M.; Watkins, Amy; Lawless, Michael; Kirkwood, Graeme J.; Saxton, Sophie N.; Eisner, David A.; Trafford, Andrew W.
Abstract: Autonomic dysregulation plays a key role in the development and progression of heart failure (HF). Vagal nerve stimulation (VNS) may be a promising therapeutic approach. However, the outcomes from clinical trials evaluating VNS in HF have been mixed, and the mechanisms underlying this treatment remain poorly understood. Intermittent high‐frequency VNS (pulse width 300 µs, 30 Hz stimulation, 30 s on, and 300 s off) was used in healthy sheep and sheep in which established HF had been induced by 4 weeks rapid ventricular pacing to assess (a) the effects of VNS on intrinsic cardiac vagal tone, (b) whether VNS delays the progression of established HF, and (c) whether high‐frequency VNS affects the regulation of cardiomyocyte calcium handling in health and disease. VNS had no effect on resting heart rate or intrinsic vagal tone in the healthy heart. Although fewer VNS‐treated animals showed subjective signs of heart failure at 6 weeks, overall VNS did not slow the progression of clinical or echocardiographic signs of HF. Chronic VNS did not affect left ventricular cardiomyocyte calcium handling in healthy sheep. Rapid ventricular pacing decreased the L‐type calcium current and calcium transient amplitude, but chronic VNS did not rescue dysfunctional calcium handling. Overall, high‐frequency VNS did not prevent progression of established HF or influence cellular excitation–contraction coupling. However, a different model of HF or selection of different stimulation parameters may have yielded different results. These results highlight the need for greater insight into VNS dosing and parameter selection and a deeper understanding of its physiological effects. Abstract : The effects of chronic vagal nerve stimulation (VNS) on cardiac function and calcium cycling were assessed in healthy sheep and sheep in which heart failure had been induced by rapid pacing. VNS did not affect calcium cycling in health or disease states and did not improve echocardiographic or biochemical markers of heart failure.